Pharmacodynamics, pharmacokinetics, and safety of ticagrelor in Chinese patients with stable coronary artery disease - Li, Haiyan (Br J Clin Pharmacol, 2016)
AIM: The aim of the study was to assess ticagrelor's effects on inhibition of platelet aggregation (IPA), P2Y(12) reaction units (PRU, measure of platelet P2Y(12) receptor blockade), pharmacokinetic (PK) parameters and safety in Chinese patients with stable coronary artery disease (CAD). METHODS: This was an open label, single centre, randomized study. Thirty‐six patients on low dose aspirin (75–100 mg day(–1)) received ticagrelor 45, 60 or 90 mg (single dose, days 1 and 7; twice daily, days 3–6). IPA (final extent), PRU and ticagrelor and AR‐C124910XX plasma concentrations were determined. RESULTS: On day 1, peak IPA >80% occurred 2–6 h post‐dose (all doses). PRU was markedly reduced at 1 h vs. baseline (all doses). With ticagrelor 45 and 90 mg twice daily, maximum IPA (mean, SD) was 91% (13%), and 99% (3%), and maximum PRU reduction from baseline (mean, SD) was 82% (17%) and 92% (9%), respectively. Approximate dose‐proportional increases (mean [%CV]; 45 vs. 90 mg twice daily) in ticagrelor C (max) (616 [37] vs. 1273 [43] ng ml(–1)) and AUC (3882 [42] vs. 8206 [51] ng ml(–1) h) and AR‐C124910XX parameters were seen. Pharmacodynamic and PK differences between 45 and 60 mg were small. No safety issues were identified. CONCLUSIONS: In Chinese patients with CAD, ticagrelor (45, 60 and 90 mg) markedly reduced platelet aggregation. The IPA and PRU magnitude increased generally with increasing doses. However, the mean pharmacodynamic differences between 45 and 60 mg doses were small. Following single and multiple doses, the mean C (max) and AUC values of ticagrelor and AR‐C124910XX increased approximately dose proportionally between 45 and 90 mg doses.